Edukasi Gizi Seimbang dan Pelatihan Pengolahan Pangan Lokal Kaya Protein sebagai Upaya Pencegahan Stunting Dini bagi Ibu Hamil dan Menyusui Desa Keruak, Lombok Timur - Diah Putri; Rohin Agra (Journal of Community Development and Empowerment, 2026)
Stunting is a child growth faltering issue caused by chronic malnutrition that requires integrated intervention from pregnancy through breastfeeding. This community service program aims to increase the knowledge of pregnant and breastfeeding mothers in Keruak Village, East Lombok, regarding balanced nutrition, as well as to train their skills in processing protein-rich local food items as an effort for early stunting prevention. The methods used included interactive education on the importance of fulfilling nutrition during the First 1,000 Days of Life (1,000 HPK) and practical workshops on processing easily accessible local foods, such as utilizing marine fish and moringa leaves into nutrient-dense daily menus. The results of this activity showed a significant 45% increase in participants' understanding of balanced nutrition concepts, as measured by comparing pre-test and post-test scores. Furthermore, participants successfully practiced creating creative, hygienic, and child-friendly processed food products. Through this program, pregnant and breastfeeding mothers became more independent in planning and serving nutritious meals for their families without relying on expensive commercial products. In conclusion, education combined with training based on local potential is effective in changing household nutrition fulfillment behaviors. This program is expected to continue through local posyandu (integrated health post) cadres to regularly monitor toddler growth and achieve a stunting-free Keruak Village.